Qualidade do sono de universitários e sua interface com a síndrome metabólica e indicadores de saúde - Araújo, Márcio Flávio Moura de (2012)
The quality of sleep is a powerful predictor of health, because it is related with the risk for chronic health problems, such as diabetes, hypertension, obesity and metabolic syndrome. This is an aggregation of cardio-metabolic problems that substantially increases human morbidity and mortality from any cause. The level of relationship between MS and the quantity/quality of sleep is already established in the elderly, middle-aged people, workers and even children, but in young adults, apparently healthy, is still unknown. Thus, the objective of this research was to analyze the relationship between MS and health indicators with the quality of sleep university in Fortaleza-Ceará. Observational quantitative research using cross-sectional design. We evaluated 701 college students from 24 courses in the six areas of knowledge of the UFC between March and June 2011 in two stages. In the first, students filled an instrument on socio-demographic and health indicators and a validated version adapted to Brazilian standards from the Pittsburgh Sleep Quality Index. In a posterior date with students fasted for twelve hours, we collected the following biochemical data: fasting venous plasma glucose, plasma triglycerides, LDL-C, HDL-C and cortisol. On the same occasion, we measured blood pressure, waist circumference, height and weight. We analyzed the components of MS based on the NCEP-ATP III. Data were triple typed and analyzed in STATA software version 8.0. A substantial amount of the college students were poor sleepers (95.2%) while a minority had MS (1.6%). Students with shorter sleep duration were in the area of land sciences (6.24h SD ± 1.23 h) and technology (6.29 h SD ± 1.24) (p=0.04). Most of the poor sleepers students (39%) had an income above six minimum wages (p=0.03). The students who lived alone (95% CI - 1.03-1.08) (p<0.001) or with parents (p<0.020), age ≥ 30 years (95% CI - 1.02-1.07) (p<0.001), with average risk for alcoholism (95% CI - 1.03-1.07) (p<0.001) and daily smokers (95% CI - 1.02-1.06) (p<0.001) presented a chance of having poor sleep quality more than 1.05, 1.05, 1.05, 1.04 and 1.05, respectively. Virtually all students with elevated cortisol levels (96.1%) had sleep efficiency with 65-74% (p=0.02). There is a 5% increase in the probability of poor sleepers college students develop MS (PR = 1.05, 95% :1,03-1, 07) (p = 0.013). These students also have a chance greater than 1.05 to present high glucose (PR=1.05; 95% CI – 1.03-1.07) (p<0.001). There was no statistically significant correlation between the individual components of MS and the PSQI. Therefore, the college students poor sleepers have a higher relative risk of presenting SM compared to good sleepers. It is important that health professionals consider the assessment of sleep quality of these young people to prevent and combat MS, as well as in developing individualized strategies to promote their health.